How effective is the implementation of the valproate pregnancy prevention programme in Montenegro? – A 7-year national retrospective study - Veselinka Vukićević; Snežana Mugoša; Gordana Stanojević; Sandra Vezmar Kovačević (Therapeutic Advances in Drug Safety)
Background: Valproate (valproic acid, sodium valproate) is authorised in Montenegro for epilepsy and bipolar disorder treatment. Due to known teratogenicity, risk minimisation measures were introduced in 2014 and further reinforced in 2018 by the implementation of the Pregnancy Prevention Programme (PPP). Despite these measures, consumption of valproate in Montenegro increased in the period 2016–2022. Objectives: To investigate the effects of risk minimisation measures on valproate prescription in Montenegro. Design: A retrospective, observational, 7-year, nationwide study. Methods: The Primary Health Care Information System (PHCIS) was used as a data source. The health records of women of childbearing potential (12–55 years) for the period 2016–2022 were analysed. Additionally, unstructured data were reviewed to determine the number and characteristics of valproate-exposed pregnancies. The software PASW, version 25.0 (SPSS Inc., Chicago, IL, USA) was used for the statistical analysis. Results: A total of 2247 women of childbearing potential using valproate were identified during the observed period. The number of patients using valproate for epilepsy treatment decreased by 24% while the use of valproate in psychiatry increased by 45% over the observed period. The age of the patient was the only predictive factor for successful PPP implementation (chi-square = 35.811, df = 4 and p  < 0.001). The odds ratio (OR) for the age category was 1.22 (95% CI: 1.10–1.35). Contraception prescription was recorded in only 1.5% of patients following the PPP implementation. A total of 11 cases of exposed pregnancies were identified, while epilepsy was the indication in 5 (45%) cases. Conclusion: Regulatory risk minimisation measures had a limited impact on reducing the risk of valproate teratogenicity in Montenegro, with the most success in the group of youngest patients. Measures were more effective in the epilepsy indication. The rising use of valproate for psychiatric indications is concerning. Targeted education, better preconception care and improved coordination among healthcare professionals are necessary.